1999
DOI: 10.1006/viro.1999.9869
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Is a Powerful Inhibitor of in Vivo HIV-1 Infection and Preserves Human CD4+ T Cells from Virus-Induced Depletion in SCID Mice Transplanted with Human Cells

Abstract: Although several studies are available on the in vitro inhibitory activities of type I interferon (IFN) on HIV-1 replication, the role of these cytokines in the pathogenesis of AIDS is still matter of conjecture. Both beneficial and adverse effects have been envisaged and considered as a possible rationale for the development of either IFN or anti-IFN therapies in HIV-1-infected patients. In the present study, we have evaluated the efficacy of human type I IFN on HIV-1 infection and virus-induced depletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 36 publications
(48 reference statements)
0
29
0
2
Order By: Relevance
“…3A). Based on several reports, including ours, describing a profound impairment in IFN-␣ production by PDC during chronic viremia following TLR engagement (13,14,49) and because IRF-7 has been identified as the key player in induced type I IFN production (45, 46), we measured levels of intracellular IRF-7 in PDC. Using a polyclonal antibody that recognizes total IRF-7 (phosphorylated and unphosphorylated forms [16,31,56]), we observed that the constitutive intracellular levels of IRF-7 were lower in circulating PDC from chronically HIV-1-infected subjects than in those from uninfected control subjects (P Ͻ 0.002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3A). Based on several reports, including ours, describing a profound impairment in IFN-␣ production by PDC during chronic viremia following TLR engagement (13,14,49) and because IRF-7 has been identified as the key player in induced type I IFN production (45, 46), we measured levels of intracellular IRF-7 in PDC. Using a polyclonal antibody that recognizes total IRF-7 (phosphorylated and unphosphorylated forms [16,31,56]), we observed that the constitutive intracellular levels of IRF-7 were lower in circulating PDC from chronically HIV-1-infected subjects than in those from uninfected control subjects (P Ͻ 0.002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ϩ T cells (49). Thus, controversy remains on the role of IFN-␣ as an indirect or direct inducer of apoptosis of CD4 ϩ T cells through PDC/TRAIL induction, whereas the possibility that IFN-␣ acts as an antiviral agent by controlling HIV-1 replication and thus reducing virally mediated T-cell loss appears to be supported by several studies (reviewed in references 26, 47, and 58).…”
mentioning
confidence: 99%
“…against these cytokines did not interfere significantly with the suppressive activity under the present assay conditions. The involvement of human IFN-␣/␤, which have been implicated in anti-HIV-1 protective activity in SCID mice (12), is also unlikely, since X4 HIV-1 infection of PBMC was not suppressed by the factor under the same experimental conditions. Since neutralizing antibodies against IL-4, IL-10, and IFN-␤ alone or in combination showed a marginal blocking effect (20 to 35%) against the present factor, it remains to be resolved whether IL-4, IL-10, and IFN-␤, which are known to suppress R5 HIV-1, work synergistically with the present HIV-1 suppressor factor or whether the factor shares epitopes with these molecules and is thus partially cross-reactive with these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…These agonists stimulate dendritic cells to produce type I interferon (IFN-α/β) and cytokines essential in the development and maintenance of immune responses. Production of IFN-α/β by pDC is essential in antiviral innate immunity through direct inhibition of viral replication (19) and induction of an antiviral state in neighboring cells (20). In addition, IFN-α has a strong adjuvant effect on a variety of immune cells including monocytes, mDC, NK cells, and B and T lymphocytes (21).…”
Section: Introductionmentioning
confidence: 99%